DESIGN AND EXPERIMENTAL STUDY OF SORGHUM CUTTING TABLES BASED ON A PUSH AND DIVISION INTEGRATED OUTER DIVIDER - Qinghao He; Duanyang Geng; Jianning Yin; Dong Yue; Lei Ni (Engenharia Agrícola)
ABSTRACT At present, there are serious problems in sorghum harvesting, such as lodging entanglement and the loss of broken stems due to the lack of an external dividing device for the cutting table and holding device. Based on the physical and mechanical characteristics of sorghum plants, an integrated outer divider was developed. The main structural parameters and working parameters of the outer divider were determined. A comparative test of the working quality of the outer divider was carried out. The results show that the working quality of the cutting table with the outer divider is obviously better than that without the outer divider and that the harvest loss of the cutting table is effectively reduced. The Box–Behnken experimental design method was used to investigate the effects of the forward speed, rotation speed of the grain lifter and dividing angle of the outer divider on the lodging and broken stem loss rates during sorghum harvesting. The regression mathematical model and response surface of the lodging and broken stem loss rates and the analysis factors were established, and the optimal working parameters of the outer divider were determined as follows: the dividing angle of the outer divider was 20°, the forward speed was 0.8 m/s, and the rotating speed of the grain lifter was 330 rpm. Under these parameters, the loss rate of the fall was 1.08%, and the loss rate of broken stems was 1.05%, which met the requirements of sorghum cutting tables